Universal Design for Learning (UDL) in Heritage Education: A Multimedia Approach to Phra Aphai Mani - Kittichai Kasemsarn; Antika Sawadsri (My University, 2024)
Even though classic literature has cultural and educational value in heritage education, students often have trouble becoming interested because of the archaic language, a lack of good learning materials, the idea that the literature is not relevant, and complicated plots. This research aims to enhance heritage education by identifying barriers and drivers in youth engagement with classic Thai literature and exploring how Universal Design for Learning (UDL) principles could be applied to increase motivation in learning classic literature through multimedia. Ten interviews with experts, 100 on-site questionnaires filled out by students aged 15–25 years, and a multimedia e-book were used together in this mixed-methods study. As a case study, the researchers asked both experts and students to read the Thai classic poem “Phra Aphai Mani: Escaping from the Sea Witch” and make suggestions for how it could be better. The results show that there are barriers to heritage education, such as ‘the story is not connected to the present’ (mean = 4.52/5), ‘archaic vocabulary and language barriers’ (mean = 4.36/5), and ‘learning materials’ (mean = 4.25/5). Surprisingly, Thai students showed more positive attitudes towards literature courses than expected based on international trends. Key drivers for enhancing heritage education include ‘classic literature in modern, easy-to-read language’ (mean = 4.65/5), ‘including multimedia’ (mean = 4.58/5), ‘the plot/story adapted to the current era’ (mean = 4.50/5), and ‘new presenting technologies’ (mean = 4.49/5). Next, as an innovative way to improve heritage education, this study developed a free e-book titled “Phra Aphai Mani: Escaping from the Sea Witch”, which includes motion graphics and other multimedia elements. This research contributes to knowledge by demonstrating how UDL can be applied to classic literature within heritage education, enhancing understanding of student needs, and creating more effective, inclusive multimedia teaching methods for preserving and transmitting cultural heritage.
Keywords: Innovations in Educational Methods